Antidiabetic and Liver Tissue Improvement Potency of Surf Redfish (Actinopyga mauritiana) in Alloxan-Induced Diabetic Mice - Arma Citra; I Nyoman Ehrich Lister; Edy Fachrial; Sahna Ferdinand Ginting (Postgraduate, University of Mataram, 2023)
Long-term hyperglycemia is associated with various organ damage. One of these damages is Non-Alcoholic Fatty Liver Disease (NAFLD). One of the potential natural products that may improve this impact is Surf Redfish. Hence this study aimed to investigate the antidiabetic and liver protection effects of Surf Redfish in some diabetic male Mice. This study was an experimental study that used 25 male mice grouped into control, standard, Surf Redfish Extract-I (100 mg/ kg BW), II (200 mg// kg BW), and III (400 mg/ kg BW). This study evaluated the blood glucose level (before and after induction, third, sixth, ninth, twelfth, and fifteenth days) and histology study of liver tissue. This study showed that the Surf Redfish ethanol extract significantly decreased blood glucose levels every day for fifteen days (P-Value < 0.05). This extract also showed a significant decrease in vacuolated degeneration after fifteen days of extract administration (P-Value). Hence, it can be concluded that the most effective dose of Surf Redfish extracts in this study was 400 mg/ kg BW to decrease blood glucose level and width of vacuolated degeneration after fifteen days of administration.